Numerical Simulation Study on Application of T-Shaped Composite Pile Support System in Super-Large Foundation Pit Support Engineering - Jiaqi Lu; Huihuang Jiang (Applied Sciences, 2023)
To reduce the impact of the one-time excavation of deep and large foundation pits on nearby subway tunnels, the excavation should be performed separately; thus, a T-shaped pile support system was studied. First, several foundation pit support structures were compared and selected, and a pile support system was proposed. In terms of space, a T-shaped support structure was formed to reduce the spatial requirements of the foundation pit. Through finite element software, a 1:1 restoration of the foundation pit using a T-shaped pile support system was carried out. The stress characteristics and support effect of the support structure were studied under two working conditions of symmetric and asymmetric excavation. The study found that there was a central effect on the foundation pit using a T-shaped pile support system, that is, the support piles farther away from the center of the T-shaped structure gradually increased the maximum pile bending moment and displacement owing to the constraints of vertical piles and the influence of the pit angle effect, respectively. In the case of symmetrical excavation, the T-shaped structure was simplified into a triangular structure, and the stress form of this type of structure could be reduced to a cantilever double-row pile structure, which met the requirements of pit excavation. The application of a T-shaped pile support structure can provide new design ideas for foundation pit engineering near regional subway lines.